Analysis of the Concept of Corruptive Factors - Primov, F. A. (European Journal of Life Safety and Stability (2660-9630), 2022)
Analyzes show that the effectiveness of the fight against corruption largely depends on how this concept is understood and how much it is expressed in practice. This word is derived from the Persian word "bribe" and means "small money", "small money", "charity" and is understood as something (money) given or given to an official for illegal settlement of a case.